1994
DOI: 10.1111/j.1526-4610.1994.hed3401044.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Tension‐Type Headache, Mood Depression and Serotonin: Therapeutic Effects of Fluvoxamine and Mianserine

Abstract: Forty out-patients affected by chronic tension-type headache were selected according to the diagnostic criteria of International Headache Society (IHS) Headache Classification Committee. In a controlled trial patients received placebo for a four-week baseline period, then they were randomized in double-blind fashion to therapy with mianserine (30-60 mg/day) of fluvoxamine (50-100 mg/day) for another eight-week period. Frequency of headache, pain severity and analgesic consumption were evaluated using a self-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 17 publications
1
35
0
1
Order By: Relevance
“…7 Manna et al found fluvoxamine was more effective than mianserine in the nondepressed subgroup of patients with more severe headache, while mianserine was more effective in depressed patients with moderate headache. 8 In the management of migraine headaches, Adly et al found those receiving fluoxetine improved without any concomitant change in their Zung Depression scores. 14 In the treatment of painful diabetic neuropathy, Sindrup et al found improvement in patients treated with paroxetine who either were not depressed or did not experience an antidepressant effect as measured by the Beck Depression Inventory.…”
Section: Study Design N Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…7 Manna et al found fluvoxamine was more effective than mianserine in the nondepressed subgroup of patients with more severe headache, while mianserine was more effective in depressed patients with moderate headache. 8 In the management of migraine headaches, Adly et al found those receiving fluoxetine improved without any concomitant change in their Zung Depression scores. 14 In the treatment of painful diabetic neuropathy, Sindrup et al found improvement in patients treated with paroxetine who either were not depressed or did not experience an antidepressant effect as measured by the Beck Depression Inventory.…”
Section: Study Design N Resultsmentioning
confidence: 98%
“…13 In Bánk's comparison of fluvoxamine and low-dose amitriptyline, patients experienced similar improvement, but fewer side effects were noted with fluvoxamine. 15 Except Manna et al, 8 no authors stratified for the presence of major depression or analyzed results separately for depressed and nondepressed groups.…”
Section: Study Design N Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 4 studies 6,132,137,141 were conducted in a primary care setting, with the remainder situated in pain, psychiatric, and specialty clinics. The intervention arm of each selected study usually involved tricyclic antidepressants, and only 4 studies involved selective serotonin reuptake inhibitors (SSRIs) 135,138,143,145 to assess pain and depression. While most of the studies demonstrated improvement in both pain and depression symptoms, a few of the studies 132,142,147 failed to show symptom relief.…”
Section: Is Antidepressant Treatment For Painful Symptoms and Comorbimentioning
confidence: 99%
“…Ein überzeugender positiver Effekt der SSRI auf die depressionsbedingten körperlichen Schmerzen konnte bisher nicht nachgewiesen werden, trotz Besserung des psychischen Zustandes unter der SSRI-Therapie [23,24]. Zusätzlich erwiesen sich SSRI als entweder unwirksam oder deutlich weniger wirksam als Trizyklika, SNRI oder Mirtazapin in der Behandlung chronischer Schmerzen anderer Genese.…”
Section: Antidepressiva In Der Therapieunclassified